Perfectionism, Self-Esteem and DSM-IV-Based Symptoms of Anxiety Disorders in Adolescents - Nadia Hameed, Saima Arzeen (Pakistan Journal of Medical & Health Sciences, 2023)
Objectives: The purpose of this study is to examine the relationship between perfectionism and self-esteem and the symptoms of anxiety disorders in adolescent. Study design: Cross-sectional research design was used in this study Place and duration of the study: The study was conducted from private high secondary schools and colleges in Karachi, Pakistan, from February 2019 to March 2020. Subject and Method: 500 students made up the entire sample for the current study. Additionally, the sample includes both male (N=212) and female (N=288) students. The participants’ ages ranged from 12 to 18 years old. The mean age of the sample as a whole was 15.44 (SD=1.82), while the mean ages of male and female students were respectively 15.12 (SD=1.89) and 15.68 (SD=1.88). Furthermore, a sample of 254 kids in grades 8 through 10 and 246 college students in grades 11 and 12 was chosen from various schools and colleges. Results: Pearson product moment correlation and linear regression were used to examine the data using statistical software for social sciences (SPSS- Vol. 16.0). The findings demonstrated that perfectionism and anxiety have a strong positive relationship (P.001). Furthermore, a summary of linear regression demonstrates that perfectionism in adolescents predicts the amount of anxiety in adolescents. Perfectionism accounts for around 5.3 percent of the variation in anxiety symptoms in adolescents. Self-esteem and anxiety, on the other hand, have a substantial negative connection (p.001) among adolescents. Low self-esteem in teenagers significantly predicts the level of anxiety in adolescents, according to the results of linear regression. Self-esteem accounts for around 15% of the variation in anxiety symptoms in adolescents. The findings were evaluated in light of prior studies, and new directions for future research were suggested. Practical Implication: The study "Perfectionism, Self-esteem, and DSM-IV-Based Symptoms of Anxiety Disorders in Adolescents" has important implications for those working with anxious adolescents in the Pakistani community. The results suggest that reducing perfectionism and improving self-esteem could help alleviate anxiety symptoms in Pakistani adolescents, and mental health practitioners can use this information to develop culturally sensitive interventions that take into account the unique cultural and social context of Pakistan. Additionally, early detection and intervention of anxiety symptoms is crucial, and raising awareness among parents, teachers, and healthcare professionals in Pakistan could be beneficial. The study’s findings could inform the development of effective, culturally sensitive mental health programs and interventions for Pakistani adolescents in the educational system. Overall, this study provides valuable information to assist parents and professionals in supporting adolescents coping with anxiety challenges. Conclusion: The study provides valuable information for parents and professionals to support adolescents coping with anxiety challenges, but it also has some limitations, and important recommendations were made. Keywords Self-esteem, Perfectionism, Anxiety disorder, Adolescents, DSM-IV-TR,